Single and multiple liver abscesses in adults in Delhi are amoebic in origin: a clinical and microbiological study. (April 2013) - Tayal, Anshula; Lal, Pawanindra; Uppal, Beena
Single and multiple liver abscesses in Delhi are predominantly amoebic and must be distinguished from pyogenic abscesses which frequently require drainage. Mixed abscesses are larger, harbouring Gram negative rods. Multiple abscesses are not always pyogenic and presence of bacteria does not imply a primary pyogenic source.